Concepção de tecnologia dos Programas São Paulo Faz Escola e Inova Educação: permanências ou rupturas? - Beriotto, Siméia de Souza (Universidade Federal de São Carlos, 2022)
The driving element of this research arises in the context of emphasis on the technology theme in educational programs and policies that guide the school curriculum. Affiliated to the State, Politics and Human Formation line of the Graduate Program in Education at the Federal University of São Carlos, the present investigation analyzed the focus attributed to technologies in the São Paulo Faz Escola and Inova Educação Programs, implemented in the state education network supposedly with the aim of improving the quality of education. In response to the question “What role or roles have been attributed to technology in education according to the conception/s disseminated in state schools in São Paulo by the curricular programs of the State of São Paulo - Programs São Paulo Faz Escola and Inova Educação? ”, the general objective of this investigation was to identify and compare the conception/s of technology present in the São Paulo Faz Escola and Inova Educação Programs, seeking to understand in this process possible continuities and ruptures. Articulated to the general objective of this study, specific objectives were outlined that proposed to understand the implications generated by the transformations of the productive process of contemporary capitalism and neoliberal policy in the organization of the school curriculum and in the proposition of technological education; to analyze the structure and functioning of the São Paulo Faz Escola and Inova Educação Programs; to understand and analyze the concept of technological education in the São Paulo Faz Escola and Inova Educação Programs, as well as to compare the concept/s of technology that permeate these Programs. Thus, based on dialectical historical materialism, the qualitative biographical and documental analysis, carried out from the method and content categories, sought to analyze the structure and functioning of the Programs in order to identify approaches to the technology theme with assumptions political-pedagogical approaches focused on managerialism and the subordination of education to the ideological project of adapting subjects to the new technical base of capital. To support the proposed investigation, a comparative analysis was carried out between the two Programs, the result of which indicated differences and permanence in the proposition of technological education offered by both. Organized under technological determinism and utilitarianism, it was found that the technological education proposed by São Paulo Faz Escola, when crossing the areas of knowledge, indicates from the articulation of theory with practice and the use of Information and Communication Technologies (ICT), the development of skills and abilities associated with technologies linked to school knowledge. In the Inova Educação Program, technological education presented from the Technology and Innovation curricular component, based on intellectualism and technological instrumentalism, is presented as part of culture. Thus, materialized in the integration of the areas of Digital Information and Communication Technologies (TDIC), Digital Literacy and Computational Thinking, the technological education of the Inova Program emphasizes the practical teaching of knowledge, the Digital Information and Communication Technologies (TDIC) and the development of specific competences and abilities of the axes that compose it. However, the continued absence of investments in infrastructure and connectivity, as well as the proposition of a training aimed at adapting subjects to the demands of capital in both curricular policies, proved to be, with the exception of differences, insufficient to characterize, in some way, a rupture with the education project undertaken by the state education network focused on the formation of subjects capable of employability and entrepreneurship in an increasingly technological society with growing structural unemployment.
Conception of technology in the São Paulo Faz Escola and Inova Educação Programs: continuity or rupture?
Keywords: Tecnologia; Currículo; Programa São Paulo Faz Escola; Programa Inova Educação; Technology; Curriculum; São Paulo Faz Escola Program; Inova Education Program; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::CURRICULO::CURRICULOS ESPECIFICOS PARA NIVEIS E TIPOS DE EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::CURRICULO::TEORIA GERAL DE PLANEJAMENTO E DESENVOLVIMENTO CURRICULAR; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA DOS RECURSOS HUMANOS::MERCADO DE TRABALHO; POLITICA DO GOVERNO; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::TECNOLOGIA EDUCACIONAL; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO::ESTRUTURA E TRANSFORMACAO DO ESTADO